Fermentasi daun mangrove Rhizophora mucronata sebagai teh herbal : Fermentation of mangrove leaves (Rhizophora mucronata) as herbal tea - Lein, Marianus Ada; Desniar, Desniar; Hardiningtyas, Safrina Dyah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Rhizophora mucronata is a type of mangrove commonly found in Indonesia. The leaves of this plant contain various secondary metabolites, such as tannins, carotenoids, phenols, chlorophyll, and alkaloids, which have the potential to be used as ingredients in fermented herbal tea. Tannin compounds are safe for consumption and have various functions, including antioxidant, antibacterial, anticancer, and anti-allergic properties.  This study aims to determine the optimal fermentation time for mangrove leaves as a raw material for herbal tea using the BAL Lactobacillus plantarum SK (5) starter. A completely randomized design (CRD) was used with fermentation duration treatments (0, 1, 2, 3, and 4 days) and three replications. The characteristics of the raw materials were tested for heavy metals, moisture content, ash, and phytochemicals. The research on herbal tea production involved mixing mangrove leaves (20 g) and aquades (60 mL), adding a starter (10% (v/b)), and then fermenting for four days at a temperature of 37°C. Analysis includes the measurement of pH, total titratable acidity (TTA), total bacteria, and total lactic acid bacteria (LAB). The heavy metal content, moisture content, and ash of the mangrove leaves meet SNI requirements. Flavonoid, phenol, saponin, tannin, and steroid compounds were detected in the raw material and fermentation product of R. mucronata mangrove leaves.  The best fermentation time was obtained on the second day with a pH value of 4.9, TAT of 2.4%, and total BAL (1.7 log CFU/mL). The treatment duration of mangrove leaf fermentation showed changes in pH, TAT, total bacteria, and total BAL values during the fermentation process.  The pH value, TAT, total bacteria, and total BAL during the fermentation process indicate that mangrove leaves have the potential to be used as fermented herbal tea.